Advancing the Payments for Ecosystem Service Discourse through Institutional Theory - Kristjan Johannes Suse Jespersen (Copenhagen Business School (CBS), 2017)
My research interest centers on payments for ecosystem services (PES), a prominent strategy to address economic externalities of resource extraction and commodity processing, improving both social and ecological outcomes. Given the novelty of these kinds of institutions, my research uses them as a set of compelling cases for studying institutional creation, and my driving research question is “How are institutions in support of PES created?” Importantly, my research spans environmental economics and business studies to study how PES schemes might more fully incorporate the private sector, an outcome that will be essential to their success. In the face of widespread enthusiasm, PES still has faced considerable legitimate critique. My research agenda is focused on a critical analysis of the development of PES from the perspective of organizational institutionalism. I principally use the literature on institutional work, which serves as a lens for understanding the reorganisation of existing practices and norms (Lawrence & Suddaby, 2006). The research seeks to offer a unique contribution by interpreting PES through a neo-institutional perspective. Through both qualitative and quantitative approaches, the work identifies a key flaw in many current studies of PES: a thin conception of institutions as rules that ignores more subtle ways in which institutions and power are involved in the creation of PES systems. This dissertation is comprised of four papers each contributing to the debate on PES by drawing insights from the institutional theory literature. Comprised of a meta-analysis literature review, two case studies and a contextual theory-driven paper, the findings are applicable for both PES scholars and practitioners. By engaging in this new perspective, PES scholars and practitioners will better understand how less frequently or easily observed institutions and forms of power can affect the development and effectiveness of PES initiatives. Collectively, the findings indicate that in order for PES to become a successful tool for sustainability, it must break from singularly using rational action and transaction cost theory as governing theories. The research offers recommendations to conceptually reframe PES as a tool for enabling sustainable relationships with nature, conserving and restoring ecosystems and their benefits for people.
hdl:10398/9499
Keywords: 650